2013
DOI: 10.1161/strokeaha.113.002477
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variant RNF213 c.14576G>A in Various Phenotypes of Intracranial Major Artery Stenosis/Occlusion

Abstract: Background and Purpose-Recently, we reported a common genetic variant, ring finger protein 213 (RNF213) c.14576G>Avariant, a susceptibility gene for moyamoya disease (MMD), among patients with intracranial major artery stenosis/ occlusion (ICASO) in a selected Japanese population. The aim of this 2-center-based case-control study was to confirm our previous finding in a larger population. S.).The online-only Data Supplement is available with this article at http://stroke.ahajournals.org/lookup/suppl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
119
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(126 citation statements)
references
References 16 publications
7
119
0
Order By: Relevance
“…This study showed that the genotypes and allele frequencies of RNF213 p.R4810K in the general Japanese population were 1.73 and 0.87 %, respectively, which are similar to frequencies previously reported [6][7][8][9][10][11]. Geographic distribution of RNF213 p.R4810K in East Asian populations is shown in Table 3.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This study showed that the genotypes and allele frequencies of RNF213 p.R4810K in the general Japanese population were 1.73 and 0.87 %, respectively, which are similar to frequencies previously reported [6][7][8][9][10][11]. Geographic distribution of RNF213 p.R4810K in East Asian populations is shown in Table 3.…”
Section: Discussionsupporting
confidence: 87%
“…Recently, RNF213 has been identified as a susceptibility gene for MMD. The p.R4810K polymorphism (c.14429G [ A: rs112735431) in RNF213 has a strong association with the disease in Japanese, Korean, and Chinese MMD patients [6,7], and the frequency of p.R4810K in the general Japanese population has been estimated at 1.4-2.7 % [6][7][8][9][10][11]. However, no studies have investigated symptoms and disease histories of RNF213 p.R4810K carriers in the general Japanese population, except for one report that tested the association of RNF213 p.R4810K with blood pressure [10].…”
Section: Introductionmentioning
confidence: 99%
“…It is described that conventional angiographic evaluation methods cannot easily differentiate MMD from intracranial atherosclerotic disease [15,17] and genetic analysis or high resolution MRI is useful for the differentiation [15,17]. It is well-known that Down syndrome and von Recklinghausen disease accompanies with moyamoya-like vasculopathy in the western countries.…”
Section: Discussionmentioning
confidence: 99%
“…A particular subset of Japanese patients with intracranial atherosclerotic stenosis was reported to have a c.14576G>A variant in ring finger protein 213 (RNF213), which is originally known as a susceptibility gene for moyamoya disease. 4 Lifestyle may be an another major factor; extracranial carotid stenosis has become more common in Asia these days partly because of westernization of the diet and an increase in hypercholesterolemia. 5,6 A high proportion of lacunar infarction to total stroke in Asia also indicates susceptibility to intracranial vasculopathy.…”
Section: Unique Aspects Of Acute Stroke In Asiamentioning
confidence: 99%